Diversity and genetic structure of Barbacenia pabstiana L.B.SM. & Ayensu (Velloziaceae J. Agardh) in the inselbergs of southeastern Brazil - Justino, Wénita de Souza (2021)
Inselbergs are monolithic rocks, of granitic and/or gneissic matrix, formed from continental crystalline shields that hold a high diversity of species. Many species belonging to the Velloziaceae family that occur forming mats on these rocky outcrops are well adapted to the adverse environmental conditions imposed by these inselbergs, being restricted to these rupicolous communities. Barbacenia pabstiana L.B.Sm. & Ayensu is a mat-forming species with restricted distribution, tolerant to desiccation, in inselbergs of the state of Espírito Santo in southeastern Brazil, with naturally fragmented populations. In this work we used 12 fragments of the ISRR marker, used in other species belonging to botanical families Velloziaceae, Orchidaceae and Bromelliaceae, occurring in these rocky outcrops, to evaluate the genetic diversity and structure of B. pabstiana. The number of polymorphic loci ranged from 70.86-82.29%, the expected heterozygosity and Shannon index showed no significant differences among populations, ranging from 0.161-0.192 and 0.262-0.311, respectively. The Pedra da Lajinha population showed the highest genetic diversity values, and the structure analysis demonstrates that this population harbors diversity of all the genetic variation found in the species. Thus we suggest that this population deserves special attention in future conservation strategies. Our results show high genetic similarity among geographically distant populations, suggesting that the current geographic isolation has not yet influenced the genetic structure of the populations analyzed, and that these populations would be connected in recent periods. This work will help in new studies on population genetics of species belonging to the family Velloziaceae, as well as species of other botanical families present on rocky outcrops of inselbergs, in order to guide future conservation actions and to promote new investigations on processes of population isolation. Keywords: Inselbergs. Atlantic Forest. Monocot mats. Population genetics. ISSR. Genetic diversity